Employee Performance Improvement Strategy at the Al Madinah Surakarta Foundation - Singgih Ahmad Farizi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The purpose of this study is to analyze employee performance improvement management strategies at the Al Madinah Foundation in Surakarta. This research is motivated by the importance of employee development in improving the quality of Islamic educational institutions. Many foundations experience performance stagnation due to suboptimal human resource development management. This research uses a qualitative approach with a case study method. The subjects of this study are performance improvement strategies. The key informants in this study were the Head of Personnel, the Head of Education, and several school principals, as well as permanent teachers at the foundation. Data were collected through in-depth interviews, participant observation, and documentation, then analyzed descriptively and qualitatively. The results indicate that employee development is carried out through periodic training and regular spiritual guidance. The conclusion suggests that there are several methods and strategies that can be used to improve employee performance within an organization, specifically at educational foundations. This research contributes to the development of human resource management in Islamic educational institutions.